THE EFFECT OF PEER INTERACTION AND PARENTAL ATTENTION ON STUDENTS' SOCIAL STUDY ACHIEVEMENT AT STATE MIDDLE SCHOOL 6, KEBUMEN - Amarudin Annas; Sudrajat (RADJA PUBLIKA, 2025)
This study aims to determine whether or not there is an influence of peer interaction and parental attention on the social studies learning achievement of students of SMP Negeri 6 Kebumen. This type of research is descriptive analysis with a quantitative approach. The subjects of this study included all 848 students of SMP Negeri 6 Kebumen. Data collection techniques were carried out using questionnaires and documentation. The prerequisite test for data analysis used normality test, linearity test, multicollinearity test, while the hypothesis test used multiple linear regression technique with F test. The results of the study showed that (1) there is a significant positive influence of peer interaction on the social studies learning achievement of students of SMP Negeri 6 Kebumen which is in the high category of 65%. (2) There is a significant negative influence of parental attention on the social studies learning achievement of students of SMP Negeri 6 Kebumen which is in the high category of 77%. (3) There is a significant positive influence of peer interaction and parental attention together on the social studies learning achievement of students of SMP Negeri 6 Kebumen which is in the complete category of 97% with an average value of 78.40.